Thermal vapor ablation for lung lesions in a porcine model - Henne, Erik; Ferguson, J. Scott; Mest, Robert; Herth, Felix (Respiration, 2015)
Background: Various methods for ablating peripheral lung lesions are being investigated; however, none have been successfully adapted for delivery via bronchoscopy. Vapor ablation is currently being used to bronchoscopically create lung volume reduction in emphysema patients. Objectives: In this study, an adaptation of that technology is evaluated for potential treatment of lung lesions in a live pig model. Methods: In 5 anesthetized healthy pigs, vapor of varying energy levels was delivered bronchoscopically to 66 different lung subsegments with airway diameters of 2-5 mm. Two hours after treatment, a necropsy was performed and the ablated regions were assessed for ablation and tissue structure disruption. In 6 additional pigs, vapor was applied to 3 subsegments each. To evaluate the progression of the response to treatment, 2 were kept alive for 10 days, 2 for 21 days, and 2 for 32 days. Results: Histopathological evaluation of the sections demonstrated that vapor is capable of creating a uniform field of necrosis following the subsegment anatomical boundary. The reliability of a uniform field is dependent on the level of energy delivered. An energy level that reliably creates a uniform field of necrosis was applied in chronic animals. The animals tolerated the procedure and posttreatment care. No cardiac arrhythmias, hemorrhage, stroke, respiratory distress, or pneumothorax occurred during or after treatment. Conclusions: Vapor ablation is a potentially safe and efficient means of ablating a targeted region of the lung. We hypothesize that vapor may be useful in treating lesions of the lung in humans.
Gesehen am 24.08.2020